Asynchronous handshake integration on continental global manufacturing system - Oliveira, Tiago João Pires (2022)
With the Industry 4.0 spreading through the market, Continental entered the race to reach the top and keep its position as a contender for the first place in the tire industry. Nowadays, the best way to have a software better suited for your needs is to tailor it to its needs. This was exactly what happened when Continental decided to start a team to develop its own Manufacturing Execution System. While in production state, the system presented some flaws. One of them was the service responsible for connecting the Manufacturing Execution System to each Machine, which went through a complex handshaking process. The current project addresses this problem. The goal was to develop a simpler asynchronous communication process, using Message Queuing Telemetry Transport (MQTT) as a broker and implementing microservices for the interaction. The proposal included improving the communication quality and velocity. The new solution proved to be more effective, ultimately showing that the Picasso project is a success.